A Critical Discourse Analysis of the Representation of Iraq in Media Discourse (Newspaper Headlines) - Al-saedi, Hayder (International Journal of Language and Literary Studies, 2020)
The current study aims to investigate the representation of Iraq in newspapers headlines. It investigates how the newspapers headlines had covered the Iraq – ISIS conflict. 48 headlines (data collection) were collected from two different newspapers; twenty-four headlines from an Iraqi newspaper Alsabah Newspaper and twenty-four headlines from an international newspaper AlQuds Al-Arabi Newspaper. The data were sampled and analyzed using the Ideological Square which was proposed by van Dijk (1998, 2006). The findings revealed that the sampled headlines of these two newspapers show different underlying ideologies in addressing the Iraq – ISIS conflict. It concluded that the headlines of every newspaper expressed their ideologies in a positive representation (US) and a negative representation (Them).